Metalinguistic awareness in primary schoolers in multilingual partial immersion education - Hofer, Barbara; Jessner, Ulrike; Traxl, Claudia (Frontiers in Language Sciences, 2025)
IntroductionThis paper reports selective findings from original research into the effects of early multilingual partial immersion education on children's metalinguistic awareness and performance in English.Procedure and methodThe study we present was carried out in two elementary schools in North Tyrol, Austria. Two groups of children participated in the research. Group 1 is enrolled in a multilingual instructional programme. Group 2 is in mainstream education. For Group 1 (the experimental group) English is the third language, for Group 2 (the control group) it is the second language. The study carried out by the third author explores how pupils in multilingual partial immersion programmes compare to their incipient bilingual counterparts in the control group on an English proficiency and a metalinguistic test. As part of a mixed methods approach a vocabulary knowledge test, a picture description test, and a language awareness test were administered.ResultsThe results of the study show a clear advantage for the pupils in the multilingual programme compared to those in mainstream schooling. The results are in line with previous research which found that early and extensive contact with an L2 benefits the acquisition of English as a third language and has positive effects on young learners' metalinguistic awareness.DiscussionTo contextualise our discussion and anchor the present research in terms of its theoretical grounding we first consider definitions of metalinguistic awareness (MeLA). We explain what MeLA is and what it entails, and we discuss different manifestations of MeLA and the role it plays in language(s) learning and multilingual development. The aim is to propose a situated meta-cognitive description for the development of metalinguistic awareness (MeLA.) in children with extensive language experience and to pin down possible implications of multilingual learning for MeLA and multilingual development more generally. Particular attention is given to how primary schoolers use their linguistic and metacognitive resources, and how these resources and the ability to leverage them change as a function of multilingual learning in formal instructional contexts. The findings are considered against established (and our own recent) research.